The Effect of Individualized Learning Using Digital Tools on Learning the Volleyball Serving Skill and Enhancing Attention Focus - Naji, Saif Alaa (STKIP Taman Siswa Bima, 2025)
This study investigates the impact of individualized digital learning on the development of volleyball serving skills and attentional focus among middle school students. Results revealed statistically significant improvements in both the volleyball serve and attention scores within the experimental group. The present study aims at exploring the effects of using Personalized Digital Learning on volleyball serving and selective attentional focus of (40) middle school students, aged (12-14), from Al-Thabrat Middle School. With a quasi-experimental design, two equivalent groups of participants was assigned to one of the two conditions: a) an experimental condition where they learned individually with digital content, or b) to control condition, in which were subject to traditional teaching methods. Measurement tools consisted of the standardized volleyball serve performance test and Borden–Anfimov attention scale. Pre-post scores were examined with paired and independent sample t-tests. The findings indicated that there were significant gains for the experimental group in volleyball serve performance (mean score was increased from 18.8 to 40.5; t = 12.45, p < 0.001) and attentional focus (score was increased from 150.7 to 139.1; t = 9.68, p < 0.001). Of the control participant, on average, serve performance was slightly higher following an intervention (18.1 to 33.4; t = 8.21, p < 0.001) and we found no moderation effect of attention (p = 0.221). These results highlight the combined advantage of individualized digital instruction for not only improving motor but also cognitive engagement and, thus, justify the incorporation of digital tools to develop skills in physical education.